Coexistence and Tolerance in Granada during the Almoravid Era (448–541 AH / 1056–1147 AD) - Yasin, Maali Mohammed (Journal of Humanities & Social Sciences, 2025)
The Islamic presence in Granada was not merely a superficial stage of coexistence among different religious groups, but rather a complex laboratory where declared values of tolerance interacted with the pragmatic demands of politics and economics. Tolerance was never absolute; it often functioned as a strategic tool employed by ruling powers to secure stability and prosperity. Periods of political strength encouraged openness and intellectual flourishing, while times of weakness or economic rivalry triggered restrictions and exclusion. Thus, the study of coexistence in Granada goes beyond idealized narratives and highlights the dynamic tension between principles and interests. This duality not only produced a culturally diverse and innovative society but also exposed its fragility in moments of crisis. The Andalusian experience, therefore, reveals coexistence as a historical process shaped by shifting balances of power, rather than as a static or perfect model.
Keywords: Al-Andalus; Granada; coexistence; tolerance; dhimmis; Jews; Christians; cultural diversity